Implementation of School Disaster-Safe Education Management Program at Senior High School in Batang Hari Regency - Masrianda, Masrianda; Hadiyanto, Hadiyanto; Sulistiyo, Sulistiyo; Muspawi, Muspawi; Sofwan, Sofwan; Ali, Ali (Edumaspul: Jurnal Pendidikan, 2024)
This qualitative study employing a case study methodology aims to investigate and elucidate the execution of the Disaster Safe Education Unit Program management at SMA Zulhijjah in Batang Hari Regency. The participants in the research were twelve people. Interview data was analyzed using "within case and cross-case analysis" between participants. The results showed that there are four main aspects, namely (1) Implementation of Planning (Planning) Disaster Safe Education Unit: The planning of this program begins with the establishment of specific goals and objectives related to safety and disaster mitigation in schools, this has indeed been designed by the management of SAM.S Zuhijjah in Batang Hari Regency to increase awareness, readiness, and rapid response to disasters among students and school staff at SAM.S Zuhijjah; (2) Implementation of Organizing Disaster Safe Education Unit:  The organizing process begins with the determination of a clear organizational structure for the implementation of the Disaster Safe Education Unit program. This includes the formation of a special team or committee responsible for the planning, implementation and evaluation of the program at SMA.S Zulhijjah which is poured into the Principal's Decree with a 1-year term of office; (3) Implementation of Implementing (Actuating) Disaster Safe Education Unit: During the Implementation, SMA.S Zulhijjah school established good cooperation with the surrounding community and other related parties, such as local government, disaster management agencies, and volunteer organizations, to support students and educators actively involved in the implementation of this program. They engage in diverse activities such as safety training, disaster awareness campaigns, and evacuation drills to ensure readiness for emergencies. Additionally, (4) Implementation of Supervision of the Disaster Safe Education Unit: The SPAB Team cluster at SMA S. Zulhijjah conducts regular supervision to oversee the execution of the Disaster Safe Education Unit program. This oversight encompasses monitoring evacuation drills, disaster education initiatives, and other mitigation measures. Evaluation outcomes are subsequently compiled into a formal school report. Suggestions that SMA S Zulhijjah school should consider regarding the implementation of the Disaster Safe Education Unit Program include: First, routine training and simulation; Second, provision of emergency equipment; Third, cooperation with the community; and Fourth, integration in the curriculum.